To a Better Partnership for Evidence-Based Agri-Food Policy Research. Multistakeholder Workshop Report - Akramov, Kamiljon; Ibragimov, Rustam; Anarbekov, Oyture; Yakubov, Murat; Dhehibi, Boubaker; Akramkhanov, Akmal (2023)
On December 15, 2022, the International Food Policy Research Institute (IFPRI), the International Center for Agricultural Research in the Dry Areas (ICARDA), and the International Water Management Institute (IWMI), together with the Ministry of Agriculture of the Republic of Uzbekistan, the International Strategic Centre for Agri-Food Development (ISCAD) under the Ministry of Agriculture, and Westminster International University in Tashkent (WIUT) organized a Multistakeholder Workshop “To a Better Partnership for Evidence-based Agrifood Policy Research.” High-level policymakers, including Mr. Aziz Voitov, Minister of Agriculture of the Republic of Uzbekistan, Mr. Bakhadir Tajiyev, Chairman of the Committee on Agriculture and Water Management of the Senat of the Oliy Majlis and Mr. Ravshan Mamutov, and Chairman of the Committee on Agriculture and Water Management of the Legislative Chamber of the Oliy Majlis of the Republic of Uzbekistan attended the workshop. The Westminster International University in Tashkent hosted the workshop, and Dr. Michael Clarke, the First Deputy Rector (Academic) of the University, welcomed the workshop participants. More than 70 representatives of various stakeholders attended the workshop, including officials of key government ministries and agencies, researchers from multiple research institutes, non-governmental and non-profit organizations, and representatives of international organizations.